Child Adjustment During COVID-19: The Role of Economic Hardship, Caregiver Stress, and Pandemic Play - Thibodeau-Nielsen, Rachel B.; Palermo, Francisco; White, Rachel E.; Wilson, Alaina; Dier, Shannon (Frontiers in Psychology, 2021)
The coronavirus disease 2019 (COVID-19) led to many lifestyle changes and economic hardships for families with young children. Previous research on risk and resilience highlights that children’s adjustment to family hardships is influenced by caregiver stress, but individual child behaviors and characteristics may protect children from negative outcomes. Interestingly, many children have been reported to incorporate COVID-19 themes in their pretend play. Theory suggests children may do so to cope with pandemic-related stress, but no empirical studies have explored this possibility. The purpose of this study was to understand the process by which COVID-19 economic hardships experienced by a family are related to children’s emotional well-being and development and to investigate how this process may vary as a function of children’s engagement in pandemic-related pretend play. Caregivers (N = 99; mostly high earning families) of preschoolers ages 3-6 years (51% girls, 82% White) living in the United States participated in an online survey at two time points during the pandemic. Result revealed that COVID-19 economic hardships were related to increased caregiver stress, which, in turn, was associated with children’s emotional distress and poorer self-regulation. However, engaging in pandemic-related pretend play appeared to protect children’s well-being by weakening the adverse association between caregivers’ stress and children’s emotional distress. Thus, addressing caregiver stress levels and allowing children an outlet to cope with challenges through pretend play could have crucial protective effects on early development and well-being during times of crisis.